Surgical Treatment of Sacroiliac Pigment Villous Nodular Synovitis: A Case Report and Literature Review - Song, Jiashi; Jiang, Kunpeng; Lv, Zhanhu; Liu, Bing (Frontiers in Surgery, 2022)
Pigmented villonodular synovitis is a rare and disabling disease that is thought to occur mostly in the knee joint. Here, the authors first present a unique case of pigmented villonodular synovitis occurring at the sacroiliac joint.The patient complained of sacroiliac joint pain with mild swelling.CT and MRI showed that the tumor was approximately 63mm by 91mm by 107mm in size and was considered to be fibrous borderline or low-grade malignancy. Intraoperative macroscopic features of the synovitis during operation suggested pigmented villonodular synovitis, which was confirmed by histopathological examination. The clinical symptoms and signs of the disease in this case are not obvious, and radiological investigations, including magnetic resonance imaging suggests high aggressiveness. The author believes that it may be more likely to relapse and metastasis, and recommends complete removal of the synovial membrane and regular follow-up, while preoperative or postoperative radiotherapy and molecular targeted therapy are not recommended for the time being. Keywords:Sacroiliac joint,pigmented villonodular synovitis ,clinical manifestations,differential diagnosis,Surgical treatment,invasive analysis ，the prognosis .